Unveiling the future of carbon pricing in Malaysia: an analysis of the legal framework for carbon taxation - Abdullah, Sarah Munirah; Mustafa, Maizatun (e-IPH Ltd, 2025)
The disastrous climate change consequences caused by greenhouse gas (GHG) emissions are very concerning. This paper aims to assess the efficacy of carbon taxation in controlling GHG emissions within Malaysia's strategy for mitigating climate change. Through an in-depth analysis of the legal framework surrounding carbon taxation, the paper provides insights into the prospects and challenges associated with implementing such a mechanism upon comparing it with carbon taxation initiatives globally, concluding that Malaysia should implement a carbon tax system to effectively reduce the country’s GHG emissions by adopting a carbon tax legal instrument for a more carbon-responsible future in Malaysia.